Impact of pharmacists as immunizers on influenza vaccination coverage in Nova Scotia, Canada. Issue 5 (3rd May 2016) - Isenor, Jennifer E.; Alia, Tania A.; Killen, Jessica L.; Billard, Beverly A.; Halperin, Beth A.; Slayter, Kathryn L.; McNeil, Shelly A.; MacDougall, Donna; Bowles, Susan K.
ABSTRACT: Immunization coverage in Canada has continued to fall below national goals. The addition of pharmacists as immunizers may increase immunization coverage. This study aimed to compare estimated influenza vaccine coverage before and after pharmacists began administering publicly funded influenza immunizations in Nova Scotia, Canada. Vaccination coverage rates and recipient demographics for the influenza vaccination seasons 2010-2011 to 2012-2013 were compared with the 2013-2014 season, the first year pharmacists provided immunizations. In 2013-2014, the vaccination coverage rate for those ≥5 years of age increased 6%, from 36% in 2012-2013 to 42% (p<0.001). Pharmacists administered over 78, 000 influenza vaccinations, nearly 9% of the province's population over the age of five. Influenza vaccine coverage rates for those ≥65 increased by 9.8% (p<0.001) in 2013-2014 compared to 2012-2013. Influenza vaccination coverage in Nova Scotia increased in 2013-2014 compared to previous years with a universal influenza program. Various factors may have contributed to the increased coverage, including the addition of pharmacists as immunizers and media coverage of influenza related fatalities. Future research will be necessary to fully determine the impact of pharmacists as immunizers.